2016
DOI: 10.1103/physrevd.93.105003
|View full text |Cite
|
Sign up to set email alerts
|

Compton scatteringSmatrix and cross section in strong magnetic field

Abstract: the ground to the arbitrary exited state was calculated by Daugherty & Harding [20] and by Meszaros [21]. However, these QED calculations assume infinitely long-lived intermediate state and, therefore, are more relevant to photon energies far from the resonances. In order to calculate the resonant cross section one has to introduce a finite lifetime or decay width to the virtual electrons for cyclotronic transitions to lower Landau levels [22]. For the specific case of ground-state to ground-state transition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 77 publications
0
44
0
Order By: Relevance
“…The resonant scattering cross-section of the X-mode photons is higher than the resonant scattering cross-section of the O-mode photons (Canuto et al 1971;Nagel 1981;Mushtukov et al 2015a). As a result, the emission around the cyclotron line should be dominated by the O-mode photons.…”
Section: The Opacity Of Moving Plasma Near the Resonance Energymentioning
confidence: 96%
See 2 more Smart Citations
“…The resonant scattering cross-section of the X-mode photons is higher than the resonant scattering cross-section of the O-mode photons (Canuto et al 1971;Nagel 1981;Mushtukov et al 2015a). As a result, the emission around the cyclotron line should be dominated by the O-mode photons.…”
Section: The Opacity Of Moving Plasma Near the Resonance Energymentioning
confidence: 96%
“…The scattering cross section σ (E, θ, y) depends on the local temperature T (y) as well. We use the scattering cross-section computed using second order perturbation theory of quantum-electrodynamics (Daugherty & Harding 1986;Harding & Daugherty 1991;Mushtukov et al 2012Mushtukov et al , 2015a.…”
Section: The Opacity Of Moving Plasma Near the Resonance Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate calculations of the Eddington flux require accounting for special features of Compton scattering in a strong magnetic field (see e.g. Herold 1979;Daugherty & Harding 1986;Mushtukov et al 2016), which is behind the scape of this letter.…”
Section: The Eddington Flux Affected By Electron-positron Pairsmentioning
confidence: 99%
“…The plasma is channeled to the polar caps by the magnetic field of the neutron star which has also profound effect on the observed X-ray spectra. In particular, the motion of the electrons in strong magnetic field is quantised, which gives rise to the so-called cyclotron resonance scattering features (CRSFs, see Mushtukov et al (2016) for a recent review). A single (fundamental) or multiple harmonics (Santangelo et al 1999) absorption-like features can be observed in X-ray band depending on the conditions in the line forming region.…”
Section: Introductionmentioning
confidence: 99%